2017
DOI: 10.1093/ntr/ntx169
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions and Misconceptions of Child Tobacco Smoke Exposure

Abstract: This study is registered as a Phase I study which is part of a larger research endeavor entitled: A program to protect young children from tobacco smoke exposure. Registration number: NCT01335178.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
3
37
1
Order By: Relevance
“…34 In addition, their previous experience of healthy babies born with paternal smoking during pregnancy and postpartum was at odds with the advice given by health professionals, which may increase their suspicions about the risks of smoking, and consequently weaken their motivation to quit smoking. 11,33,35 Health care professionals should therefore pay more attention to men who are not the rst-time expectant fathers by assessing their intention to quit smoking so as to develop effective interventions to motivate them to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, their previous experience of healthy babies born with paternal smoking during pregnancy and postpartum was at odds with the advice given by health professionals, which may increase their suspicions about the risks of smoking, and consequently weaken their motivation to quit smoking. 11,33,35 Health care professionals should therefore pay more attention to men who are not the rst-time expectant fathers by assessing their intention to quit smoking so as to develop effective interventions to motivate them to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation towards SHSe prevention included three subcategories: benefits (Hoehn, Riekert, Borrelli, Rand, & Eakin, ; Passey et al, ; Wang et al, ), shaping children's behaviour (Hoehn et al, ; Passey et al, ) and parental responsibility (Centers for Diease Control & Prevention, ; Hoehn et al, ). Parental suggestions of SHSe prevention were reported (Centers for Diease Control & Prevention, ; Hoehn et al, ; Poland, Gastaldo, Pancham, & Ferrence, ; Rosen et al, ). To understand parents’ responses and actions towards SHSe, we categorized them by location: at home, in public areas and in non‐smoking areas.…”
Section: The Studymentioning
confidence: 99%
“…Motivation is defined as a fundamental construct that provides a rationale regarding why people engage in specific behaviours (Deci & Ryan, ). Rosen et al () considered diverse perspectives and motivations of people in different locations with SHS. They found that limited competency in terms of taking protective action was due to misconceptions about exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 -15 Early developmental phases included systematic literature reviews 5 -7 and qualitative research. 7,16 On the basis of early findings revealing that parents may be unaware of the true extent of exposure, 16 we focused the developed program on providing objective information about child exposure via biomarkers and home air quality, in the context of motivational interviews (MIs). The goal of the pilot study was to assess the feasibility of the developed intervention and obtain an estimate of intervention effectiveness.…”
mentioning
confidence: 99%